Method for regulating and controlling strength and plasticity of FeMnCrCo-series high-entropy alloy based on pre-introduction of multi-dimensional crystallography defects
By introducing multi-dimensional crystallographic defects in the preparation process of FeMnCrCo series high-entropy alloys, the initial state microstructure is regulated, and the limitations of the strength plastic matching of traditional high-entropy alloys are solved, and high strength and high plasticity are achieved. It is suitable for aerospace, energy equipment and extreme service environments.
Patent Information
- Application Number
- CN202510776942.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2025-08-29
AI Technical Summary
In the existing research on the plasticity regulation of strength of high-entropy alloys, traditional strategies have limitations in single-dimensional regulation. There is a lack of systematic research on the intrinsic influence mechanism of the initial microstructure on the plasticity matching of alloy strength. In addition, parameter fluctuations in the FeMnCrCo-based metastable high-entropy alloys caused changes in crystallographic defect types and distributions, resulting in a strength plastic imbalance.
By introducing multi-dimensional crystallographic defects in the traditional plate preparation process, using homogenization treatment, forging, hot rolling, cold rolling and interpass annealing treatment and supplemented with water-cooled quenching, the crystallographic defect types, density and spatial distribution in the initial microstructure of FeMnCrCo-based high-entropy alloys are regulated, and a multi-dimensional defect strengthening mechanism is constructed.
The high strength and high plasticity matching of FeMnCrCo-based high-entropy alloy at room temperature is achieved, with a uniform elongation of more than 20%, a tensile strength of more than 600MPa, and excellent mechanical performance.
Smart Images

Figure CN120555858A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high entropy alloy materials, and in particular to a method for controlling the strength and plasticity of FeMnCrCo-based high entropy alloys based on pre-introduction of multi-dimensional crystallographic defects. Background Art
[0002] In recent years, high-entropy alloys (HEAs) have sparked extensive research in materials science due to their exceptional mechanical properties. As an innovative approach to break away from traditional alloy design, HEAs aim to maximize the configurational entropy of the alloy system by mixing multiple principal elements in equiatomic or near-equiatomic ratios, thereby achieving a large-area solid solution single-phase microstructure. During this process, the synergistic effects of the multiple alloying elements induce significant lattice distortion and diffusion kinetic hysteresis, two mechanisms believed to be key factors in endowing HEAs with high thermal stability and excellent mechanical properties. Based on this theoretical framework, early HEA design guidelines explicitly mandated the inclusion of at least five principal elements, with the atomic concentrations of each element in equiatomic or near-equiatomic ratios. However, as HEA research progressed, the traditional design philosophy of strictly adhering to equimolar ratios and a single-phase structure gradually became apparent. From the perspective of material strengthening mechanisms, single-phase HEAs primarily rely on solid solution strengthening and dislocation strengthening. This strengthening mode, while improving strength, often results in a significant decrease in ductility, making it difficult to achieve a synergistic optimization of strength and ductility. On the other hand, recent advances in thermodynamics suggest that mixing entropy is not the sole controlling factor in determining alloy phase stability. To address the above challenges, researchers introduced the theory of "metastable engineering" into the field of high-entropy alloy design and successfully developed a phase-transformation-induced plasticity high-entropy alloy system with a face-centered cubic and hexagonal close-packed dual-phase structure. This new type of alloy cleverly couples multiple deformation mechanisms such as martensitic phase transformation, twinning, stacking fault formation, and dislocation slip. The introduction of the concept of "metastable engineering" not only enriches the design theory of high-entropy alloys, but also provides a new approach to the development of new structural materials with excellent comprehensive performance. This innovative strategy is expected to promote the engineering application of high-entropy alloys in aerospace, energy equipment, and extreme service environments, and provide an effective solution to the high-performance requirements that are difficult to meet with traditional alloy materials.
[0003] During the plastic deformation of metal materials, crystal defects, as inevitable microstructural features, have a significant negative impact on their room temperature mechanical properties. Based on the geometric dimensions of crystal defects, they can be systematically divided into three typical defect systems: point defects, as the most basic defect form in crystals, include vacancies, interstitial atoms, and impurity atoms; line defects, i.e., one-dimensional defects, are mainly manifested as various types of dislocations; and surface defects are two-dimensional defects, with twin boundaries, stacking faults, and other typical representatives. In actual metal materials, these three types of crystal defects often coexist and influence each other through complex interaction mechanisms. During the room temperature deformation of metal materials, crystal defects, as sensitive areas of stress concentration, significantly change the stress field distribution inside the material. When the degree of stress concentration exceeds the interatomic bonding force, microcracks will preferentially initiate at the defects, which in turn trigger crack propagation and material failure.
[0004] Li Zhiming prepared TRIP-DP-HEA by reducing the nickel content and regulating the manganese content. When the manganese content reached 30 at.%, the alloy formed a face-centered cubic and hexagonal close-packed dual-phase structure. Mechanical property testing showed that even in its coarse-grained state, the strength and ductility of this dual-phase high-entropy alloy far exceeded those of a single-phase face-centered cubic CoCrFeMnNi high-entropy alloy, and the performance was further improved with grain refinement. By analyzing and revealing its deformation mechanism, it was found that the face-centered cubic phase undergoes martensitic transformation in the early stage of deformation, dislocation plasticity and phase transformation-induced plasticity work together, and the close-packed hexagonal phase participates in plastic deformation and hardening through dislocation slip, twinning and stacking fault formation in the later stage. The TRIP-DP-HEA designed in this study has both high strength and high ductility (ZMLi, KGPradeep, Y.Deng, D.Raabe, CCTasan, Metastable high-entropy dual-phase alloys overcome the strength-ductility trade-off, Nature. 534 (2016) 227-230.).
[0005] In summary, the existing technology still has the following problems: 1. In the research field of strength and plasticity control of high entropy alloys, the research directions are mostly focused on grain size optimization and strengthening and toughening by controlling the phase transformation behavior during deformation. However, such traditional control strategies still have certain limitations when improving the room temperature strength or / and room temperature plasticity of alloys in a single dimension. The main reason is that the intrinsic influence mechanism of the initial microstructure on the strength and plasticity matching of the alloy still lacks systematic and in-depth research. 2. In the FeMnCrCo system metastable high entropy alloys, the control of crystallographic defects in the initial microstructure still faces challenges. The initial microstructure of the alloy in this system shows a strong dependence on the processing technology. Slight fluctuations in parameters during mechanical processing and heat treatment may cause significant changes in the initial microstructure and the type, density and spatial distribution of crystallographic defects, thereby increasing the complexity and difficulty of the directional control of crystallographic defects. 3. The strength and plasticity of the FeMnCrCo system metastable high entropy alloys are significantly sensitive to the timing and type of introduction of crystal defects. During the deformation process, stress concentration is easily generated in the crystal defect area, which becomes the preferential site for microcrack initiation, thereby leading to an imbalance in the strength-plasticity matching of the alloy. Summary of the Invention
[0006] In view of this, in order to break through the dual bottlenecks of insufficient understanding of the initial microstructure and strength-plasticity matching mechanism in the field of high-entropy alloys and the lack of precise control technology for crystallographic defects, the present invention discloses a method for achieving strong plasticity control of FeMnCrCo high-entropy alloys based on the pre-introduction of multi-dimensional crystallographic defects. This method introduces an interpass annealing treatment and supplements it with water-cooling quenching in the cold rolling process of the traditional plate preparation process, homogenization treatment → forging → hot rolling → cold rolling → heat treatment, retains the multi-dimensional crystallographic defects generated during the cold rolling process in the initial microstructure of the FeMnCrCo metastable high-entropy alloy, and controls the type, density and spatial distribution of crystallographic defects in the initial microstructure of the alloy, constructs a multi-dimensional defect strengthening mechanism, and achieves good strength-plasticity matching of the alloy.
[0007] The technical solution of the present invention:
[0008] A method for controlling the strong plasticity of an FeMnCrCo-based high-entropy alloy based on pre-introduction of multi-dimensional crystallographic defects, wherein the FeMnCrCo-based high-entropy alloy is composed of Fe, Mn, Cr, and Co elements, which, in atomic percentage, include:
[0009] Fe: 46at.%-49at.%;
[0010] Mn: 32at.%-35at.%;
[0011] Cr: 9at.%-10at.%;
[0012] Co: 8at.%-10at.%;
[0013] The atomic percentages of all elements sum to 100%.
[0014] A method for controlling the strength and plasticity of FeMnCrCo-based high-entropy alloys based on pre-introduction of multi-dimensional crystallographic defects comprises the following steps:
[0015] A) Prepare the ingredients according to the target alloy composition:
[0016] Wherein, the target alloy comprises the following components in atomic percentage:
[0017] Fe: 46at.%-49at.%;
[0018] Mn: 32at.%-35at.%;
[0019] Cr: 9at.%-10at.%;
[0020] Co: 8at.%-10at.%;
[0021] The raw materials used in the batching include: Fe ingot, Mn ingot, Cr ingot, Co ingot;
[0022] B) Furnace gas washing:
[0023] Clean the gas in the furnace before vacuum melting: evacuate the vacuum induction furnace to a vacuum degree of 0.35×10 - 2 Pa, add protective gas with a purity of 99.9%. When the protective gas pressure reaches 0.2 Pa, stop charging. This process is repeated 3 times;
[0024] C) Vacuum melting:
[0025] Add high-purity raw materials into the melting furnace, wait until all the raw materials are melted to obtain alloy melt, and stir the melt continuously to promote all alloy elements to be evenly and fully melted into the melt;
[0026] D) Casting:
[0027] The slag and oxides of the melt are skimmed off and the molten metal is poured into the metal mold slowly and evenly. After the casting is completed, it is allowed to cool naturally to form.
[0028] E) homogenizing the ingot;
[0029] F) performing forging treatment;
[0030] G) performing six hot rolling processes;
[0031] H) performing a first cold rolling process;
[0032] 1) performing a first low temperature annealing treatment;
[0033] J) performing a second cold rolling process;
[0034] K) performing a second low temperature annealing treatment;
[0035] L) performing a third cold rolling process;
[0036] M) is annealed to obtain a high entropy alloy.
[0037] Preferably, in step A), the purity of the Fe ingot is not less than 99.8%, the purity of the Mn ingot is not less than 99.8%, the purity of the Cr ingot is not less than 99.9%, and the purity of the Co ingot is not less than 99.9%.
[0038] Preferably, in step B), the protective gas is argon.
[0039] Preferably, in step C), the holding time for all metal ingots to be completely melted is 40 minutes, and the mixture is allowed to stand for 30 minutes after the holding time is completed.
[0040] Preferably, in step E), the homogenization treatment conditions are as follows: heating rate of 5° C. / min, homogenization temperature of 1200° C., holding time of 2 h, followed by water quenching.
[0041] Preferably, in step F), the forging conditions are as follows: the ingot after homogenization is descaled, the riser is cut off, and the forging temperature is 1200°C.
[0042] Preferably, in step G), six hot rolling processes are performed after forging, and the hot rolling conditions are as follows: rolling temperature is 1150° C., rolling speed is 1.5 m / s, reduction per pass is 13%, and each pass is kept warm for 10 minutes during the rolling process, finally obtaining a 10 mm thick hot-rolled plate.
[0043] Preferably, in step H), the first cold rolling process is performed after the six hot rolling processes, and the conditions of the first cold rolling process are as follows: a reduction of 20% and a rolling speed of 0.3 m / s, to obtain a cold-rolled plate of about 8 mm thickness.
[0044] Preferably, in step I), a first low-temperature annealing treatment is performed after the first cold rolling treatment, and the conditions of the first low-temperature annealing treatment are as follows: annealing temperature is 350° C.-400° C., holding time is 3 min-5 min, and cooling method is water cooling.
[0045] Preferably, in step J), a second cold rolling process is performed after the first low-temperature annealing process, and the conditions of the second cold rolling process are as follows: a reduction of 25% and a rolling speed of 0.3 m / s, to obtain a cold-rolled sheet with a thickness of about 6 mm.
[0046] Preferably, in step K), a second low-temperature annealing treatment is performed after the second cold rolling treatment, and the conditions of the second low-temperature annealing treatment are as follows: annealing temperature is 350° C.-400° C., holding time is 3 min-5 min, and cooling method is water cooling.
[0047] Preferably, in step L), a third cold rolling process is performed after the second low-temperature annealing process, and the conditions of the third cold rolling process are as follows: a reduction of 17% and a rolling speed of 0.3 m / s, and finally a cold-rolled plate with a thickness of about 5 mm is obtained.
[0048] Preferably, in step M), annealing is performed after the third cold rolling process, and the annealing conditions are as follows: annealing temperature is 800° C.-1000° C., holding time is 3 min-20 min, and cooling method is water cooling.
[0049] The present invention also provides a FeMnCrCo system metastable high entropy alloy, which is obtained by the above-mentioned method for controlling the strong plasticity of the FeMnCrCo system high entropy alloy based on the pre-introduction of multi-dimensional crystallographic defects.
[0050] The key points of this invention are: pre-introducing multidimensional crystallographic defects into the initial microstructure, rationally designing the proportions of each component, and introducing an interpass annealing treatment, supplemented by water-cooling quenching, during the cold rolling step of the traditional sheet metal production process (homogenization → forging → hot rolling → cold rolling → heat treatment). This allows the multidimensional crystallographic defects generated during the cold rolling process to be retained in the initial microstructure of the alloy before mechanical property testing. Furthermore, the type, density, and spatial distribution of the crystallographic defects in the initial microstructure of the alloy are regulated, establishing a multidimensional defect strengthening mechanism and achieving an excellent balance between strength and plasticity.
[0051] Beneficial effects of the present invention: Test results show that the uniform elongation of the FeMnCrCo high entropy alloy obtained by the method of the present invention is above 20%, and the room temperature tensile strength is above 600MPa. While ensuring room temperature plasticity, it has excellent mechanical properties. Among them, the preferred alloy Fe 49 Mn 32.5 Cr 9.8 Co 8.7 The high-entropy alloy has a tensile strength of 1241 MPa and a uniform elongation of 25%, with the best comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] To clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly describes the drawings that are required to be cited in the embodiments or the description of the prior art. Obviously, the following drawings are only schematic diagrams corresponding to the embodiments of the present invention. For those of ordinary skill in the art, other relevant drawings can be obtained based on the drawings provided by the present invention without relying on creative work.
[0053] Figure 1 Room temperature mechanical properties of the alloys of Examples 1-4;
[0054] Figure 2 Fe obtained in Example 1 49 Mn 32.5 Cr 9.8 Co 8.7 Microstructural characterization of high-entropy alloys; (a) is the EBSD phase distribution map, the red area is marked as FCC (face-centered cubic crystal structure), (b) is the TEM image, DTs represents deformation twins, (c) is the TEM image, Dislocation represents dislocation;
[0055] Figure 3 Fe obtained in Example 2 48.4 Mn 33.6 Cr 9.5 Co 8.5 Microstructural characterization of high-entropy alloys; (a) is the EBSD phase distribution map, with the red area marked as FCC (face-centered cubic crystal structure), and (b) is the TEM image, with SF representing stacking faults.
[0056] Figure 4 Fe obtained in Example 3 47.5 Mn 34.2 Cr 9.4 Co 8.9 Microstructural characterization of high-entropy alloys; (a) is the EBSD phase distribution map, with the red area marked as FCC (face-centered cubic crystal structure); (b) is a TEM image, with Annealing Twin representing annealing twins; (c) is a TEM image, with SF representing stacking faults;
[0057] Figure 5 Fe obtained in Example 4 46.9 Mn 34.8 Cr 9.2 Co 9.1 Microstructural characterization of high-entropy alloys; (a) is the EBSD phase distribution map, the red area is marked as FCC (face-centered cubic crystal structure), and (b) is the TEM image. DETAILED DESCRIPTION
[0058] The technical solutions of the present invention are further described below by way of examples, but the protection scope of the present invention is not limited to the following examples.
[0059] Example 1
[0060] A Fe 49 Mn 32.5 Cr 9.8 Co 8.7 The high entropy alloy is obtained by the following method based on the pre-introduction of multi-dimensional crystallographic defects to achieve strong plasticity control of FeMnCrCo high entropy alloy.
[0061] 1) Prepare ingredients
[0062] Prepare materials with a total atomic percentage of 100% for Fe: 49 at.%, Mn: 32.5 at.%, Cr: 9.8 at.%, and Co: 8.7 at. Among them, Fe ingots with a purity of no less than 99.8%, Mn ingots with a purity of no less than 99.8%, Cr ingots with a purity of no less than 99.9%, and Co ingots with a purity of no less than 99.9% serve as the matrix raw materials for the high-entropy alloy.
[0063] 2) Preparation of high entropy alloys
[0064] According to the atomic percentage ratio, high-purity raw materials are placed in a crucible and added to the vacuum induction melting furnace for melting. Before melting, the gas in the furnace is cleaned: the vacuum induction furnace is evacuated to a vacuum degree of 0.35×10 -2 Pa, add shielding gas, argon with a purity of 99.9%. When the shielding gas pressure reaches 0.2 Pa, stop adding gas. Repeat this process three times. After all the raw materials are melted, the alloy melt is obtained. The melt is stirred continuously to ensure that all alloy elements are evenly and fully dissolved in the melt. The molten metal is slowly and evenly poured into the metal mold. After casting, it is allowed to cool naturally to form the shape.
[0065] 3) Forging and rolling of high entropy alloys
[0066] The ingots were homogenized at a heating rate of 5°C / min to a homogenization temperature of 1200°C for 2 hours, followed by water quenching. The homogenized ingots were descaled, the risers cut, and then forged at 1200°C. The forged alloys were hot-rolled in six passes at 1150°C, a rolling speed of 1.5 m / s, a 13% reduction per pass, and a 10-minute hold period between passes, resulting in 10 mm thick hot-rolled plates. The hot-rolled plates were cold-rolled in three passes at reductions of 20%, 25%, and 17%, respectively, at a rolling speed of 0.3 m / s, resulting in approximately 5 mm thick cold-rolled plates. The cold-rolled plates were annealed between passes, with the first annealing at 350°C for 3 minutes and the second annealing at 360°C for 4 minutes. Both passes were cooled with water.
[0067] 4) Heat treatment of plates
[0068] The rolled alloy plates were placed in a box-type resistance furnace for annealing at 900°C for 3 minutes using water cooling.
[0069] Fe prepared by this method 49 Mn 32.5 Cr 9.8 Co 8.7 The room temperature mechanical properties of high entropy alloy after annealing at 900℃ for 3min and water cooling are as follows: Figure 1 As shown, the yield strength is 1177MPa; the ultimate tensile strength is 1241MPa, and the uniform elongation is 25%. Figure 2 The EBSD phase image of (a) shows that the average grain size under this condition is 4.3 μm and all of it is FCC phase. Figure 2 (b)- Figure 2 The TEM image (c) shows that there are deformation twins inside the alloy before mechanical properties testing, and dislocations are entangled at the twin boundaries.
[0070] Example 2
[0071] A Fe 48.4 Mn 33.6 Cr 9.5 Co 8.5 The high entropy alloy is obtained by the following method based on the pre-introduction of multi-dimensional crystallographic defects to achieve strong plasticity control of FeMnCrCo high entropy alloy.
[0072] 1) Prepare ingredients
[0073] Prepare materials with a total atomic percentage of 100% for Fe: 48.4 at.%, Mn: 33.6 at.%, Cr: 9.5 at.%, and Co: 8.5 at. Among them, Fe ingots with a purity of no less than 99.8%, Mn ingots with a purity of no less than 99.8%, Cr ingots with a purity of no less than 99.9%, and Co ingots with a purity of no less than 99.9% serve as the matrix raw materials for the high-entropy alloy.
[0074] 2) Preparation of high entropy alloys
[0075] According to the atomic percentage ratio, high-purity raw materials are placed in a crucible and added to the vacuum induction melting furnace for melting. Before melting, the gas in the furnace is cleaned: the vacuum induction furnace is evacuated to a vacuum degree of 0.35×10 -2 Pa, add shielding gas, argon with a purity of 99.9%. When the shielding gas pressure reaches 0.2 Pa, stop adding gas. Repeat this process three times. After all the raw materials are melted, the alloy melt is obtained. The melt is stirred continuously to ensure that all alloy elements are evenly and fully dissolved in the melt. The molten metal is slowly and evenly poured into the metal mold. After casting, it is allowed to cool naturally to form the shape.
[0076] 3) Forging and rolling of high entropy alloys
[0077] The ingot was homogenized at a heating rate of 5°C / min to a homogenization temperature of 1200°C for 2 hours, followed by water quenching. The homogenized ingot was descaled, the riser removed, and then forged at 1200°C. The forged alloy was hot-rolled in six passes at 1150°C, a rolling speed of 1.5 m / s, a 13% reduction per pass, and a 10-minute hold period between passes, resulting in a 10 mm thick hot-rolled plate. The hot-rolled plate was cold-rolled in three passes at reductions of 20%, 25%, and 17%, respectively, at a rolling speed of 0.3 m / s, resulting in a cold-rolled plate approximately 5 mm thick. The cold-rolled plate was annealed between passes, with the first annealing at 360°C for 3.5 minutes and the second annealing at 370°C for 4 minutes. Both passes were cooled with water.
[0078] 4) Heat treatment of plates
[0079] The rolled alloy plates were placed in a box-type resistance furnace for annealing at 950°C for 6 minutes using water cooling.
[0080] Fe prepared by this method 48.4 Mn 33.6 Cr 9.5 Co 8.5The yield strength of the high entropy alloy is 285MPa; the ultimate tensile strength is 681MPa, and the uniform elongation is 78% (such as Figure 1 As shown). Through the analysis of the microstructure of the alloy after heat treatment, it was found that ( Figure 3 ), the average grain size of the alloy is 5 μm and all of it is FCC phase. TEM images show that there are stacking faults and annealing twins inside the alloy before mechanical properties testing, and there is no dislocation accumulation at the interface.
[0081] Example 3
[0082] A Fe 47.5 Mn 34.2 Cr 9.4 Co 8.9 The high entropy alloy is obtained by the following method based on the pre-introduction of multi-dimensional crystallographic defects to achieve strong plasticity control of FeMnCrCo high entropy alloy.
[0083] 1) Prepare ingredients
[0084] Prepare materials with a total atomic percentage of 100% for Fe: 47.5 at.%, Mn: 34.2 at.%, Cr: 9.4 at.%, and Co: 8.9 at. Among them, Fe ingots with a purity of no less than 99.8%, Mn ingots with a purity of no less than 99.8%, Cr ingots with a purity of no less than 99.9%, and Co ingots with a purity of no less than 99.9% serve as the matrix raw materials for the high-entropy alloy.
[0085] 2) Preparation of high entropy alloys
[0086] According to the atomic percentage ratio, high-purity raw materials are placed in a crucible and added to the vacuum induction melting furnace for melting. Before melting, the gas in the furnace is cleaned: the vacuum induction furnace is evacuated to a vacuum degree of 0.35×10 -2 Pa, add shielding gas, argon with a purity of 99.9%. When the shielding gas pressure reaches 0.2 Pa, stop adding gas. Repeat this process three times. After all the raw materials are melted, the alloy melt is obtained. The melt is stirred continuously to ensure that all alloy elements are evenly and fully dissolved in the melt. The molten metal is slowly and evenly poured into the metal mold. After casting, it is allowed to cool naturally to form the shape.
[0087] 3) Forging and rolling of high entropy alloys
[0088] The ingot was homogenized at a heating rate of 5°C / min to a homogenization temperature of 1200°C for 2 hours, followed by water quenching. The homogenized ingot was descaled, the riser removed, and then forged at 1200°C. The forged alloy was hot-rolled in six passes at 1150°C, a rolling speed of 1.5 m / s, a 13% reduction per pass, and a 10-minute hold period between passes, resulting in a 10 mm thick hot-rolled plate. The hot-rolled plate was cold-rolled in three passes at reductions of 20%, 25%, and 17%, respectively, at a rolling speed of 0.3 m / s, resulting in a cold-rolled plate approximately 5 mm thick. The cold-rolled plate was annealed between passes, with the first annealing at 365°C for 4 minutes and the second annealing at 375°C for 4.5 minutes. Both passes were cooled with water.
[0089] 4) Heat treatment of plates
[0090] The rolled alloy plates were placed in a box-type resistance furnace for annealing at 950°C for 15 minutes using water cooling.
[0091] Fe prepared by this method 47.5 Mn 34.2 Cr 9.4 Co 8.9 The yield strength of the high entropy alloy is 163MPa; the ultimate tensile strength is 644MPa, and the uniform elongation is 94% (such as Figure 1 As shown). Through the analysis of the microstructure of the alloy after heat treatment, it was found that ( Figure 4 ), the average grain size of the alloy is 7.5 μm and all of it is FCC phase. The TEM image shows that there are stacking faults and annealing twins inside the alloy before mechanical properties test, and there is no dislocation inside the alloy.
[0092] Example 4
[0093] A Fe 46.9 Mn 34.8 Cr 9.2 Co 9.1 The high entropy alloy is obtained by the following method based on the pre-introduction of multi-dimensional crystallographic defects to achieve strong plasticity control of FeMnCrCo high entropy alloy.
[0094] 1) Prepare ingredients
[0095] Prepare materials with a total atomic percentage of 100% for Fe: 46.9 at.%, Mn: 34.8 at.%, Cr: 9.2 at.%, and Co: 9.1 at. Among them, Fe ingots with a purity of no less than 99.8%, Mn ingots with a purity of no less than 99.8%, Cr ingots with a purity of no less than 99.9%, and Co ingots with a purity of no less than 99.9% serve as the matrix raw materials for the high-entropy alloy.
[0096] 2) Preparation of high entropy alloys
[0097] According to the atomic percentage ratio, high-purity raw materials are placed in a crucible and added to the vacuum induction melting furnace for melting. Before melting, the gas in the furnace is cleaned: the vacuum induction furnace is evacuated to a vacuum degree of 0.35×10 -2 Pa, add shielding gas, argon with a purity of 99.9%. When the shielding gas pressure reaches 0.2 Pa, stop adding gas. Repeat this process three times. After all the raw materials are melted, the alloy melt is obtained. The melt is stirred continuously to ensure that all alloy elements are evenly and fully dissolved in the melt. The molten metal is slowly and evenly poured into the metal mold. After casting, it is allowed to cool naturally to form the shape.
[0098] 3) Forging and rolling of high entropy alloys
[0099] The ingot was homogenized at a heating rate of 5°C / min to a homogenization temperature of 1200°C for 2 hours, followed by water quenching. The homogenized ingot was descaled, the riser removed, and then forged at 1200°C. The forged alloy was hot-rolled in six passes at 1150°C, a rolling speed of 1.5 m / s, a 13% reduction per pass, and a 10-minute hold period between passes, resulting in a 10 mm thick hot-rolled plate. The hot-rolled plate was cold-rolled in three passes at reductions of 20%, 25%, and 17%, respectively, at a rolling speed of 0.3 m / s, resulting in a cold-rolled plate approximately 5 mm thick. The cold-rolled plate was annealed between passes, with the first annealing at 380°C for 4 minutes and the second annealing at 385°C for 4 minutes. Both passes were cooled with water.
[0100] 4) Heat treatment of plates
[0101] The rolled alloy plates were placed in a box-type resistance furnace for annealing at a temperature of 1000°C, a holding time of 10 minutes, and a water cooling method.
[0102] Fe prepared by this method 46.9 Mn 34.8 Cr 9.2 Co 9.1The yield strength of the high entropy alloy is 195MPa; the ultimate tensile strength is 620MPa, and the uniform elongation is 56% (such as Figure 1 As shown). Through the analysis of the microstructure of the alloy after heat treatment, it was found that ( Figure 5 ), the average grain size of the alloy is 14 μm and all of it is FCC phase. TEM images show that there are no stacking faults, dislocations and annealing twins in the alloy before mechanical properties testing.
[0103] Comparing Examples 1, 2, 3, and 4, the yield strength and ultimate tensile strength of the high-entropy alloy prepared in Example 1 are significantly greater than those in Examples 2, 3, and 4. The tensile strength of Example 4 is nearly identical to that of Example 3, but the uniform elongation is 38% lower. While the uniform elongation of Example 2 is similar to that of Example 3, the strength improvement is not significant. Therefore, considering the alloy's compatibility with practical engineering requirements, Example 1 demonstrates a significant advantage.
[0104] The present invention introduces an interpass annealing treatment and supplements it with water-cooling quenching in the cold rolling process of the traditional plate preparation process (homogenization treatment → forging → hot rolling → cold rolling → heat treatment). The multidimensional crystallographic defects generated during the cold rolling process are retained in the initial microstructure of the FeMnCrCo metastable high-entropy alloy, and the type, density and spatial distribution of the crystallographic defects are regulated to construct a multidimensional defect strengthening mechanism to achieve a good strength-ductility match of the alloy. In addition, the preparation method of the present invention adopts a process that combines rolling and heat treatment conventionally used in the industry. The process is simple and feasible, and is suitable for industrial production.
Claims
1. A method for controlling the strength and plasticity of FeMnCrCo high entropy alloys based on the pre-introduction of multi-dimensional crystallographic defects, characterized in that: The following steps are involved: A) Ingredients; B) Cleaning the vacuum induction furnace with argon gas; C) Vacuum melting; D) casting; E) homogenizing the ingot; F) performing forging treatment; G) performing six hot rolling processes; H) performing a first cold rolling process; 1) performing a first low temperature annealing treatment; J) performing a second cold rolling process; K) performing a second low temperature annealing treatment; L) performing a third cold rolling process; M) is annealed to obtain a high entropy alloy.
2. The method for controlling the strength and plasticity of FeMnCrCo high entropy alloys based on pre-introduction of multi-dimensional crystallographic defects according to claim 1, characterized in that: In step A), the ingredients are prepared according to the target alloy composition: The target alloy includes the following components in atomic percentage: Fe: 46at.%-49at.%; Mn: 32at.%-35at.%; Cr: 9at.%-10at.%; Co: 8at.%-10at.%; The raw materials used in the batching include: Fe ingots, Mn ingots, Cr ingots, and Co ingots.
3. The method for controlling the strength and plasticity of FeMnCrCo high entropy alloys based on pre-introduction of multi-dimensional crystallographic defects according to claim 1, characterized in that: In step E), the homogenization treatment conditions are: heating rate of 5°C / min, homogenization temperature of 1200°C, holding time of 2 hours, and subsequent water quenching. In step G), after forging, six hot rolling treatments are performed. The hot rolling treatment conditions are: rolling temperature of 1150°C, rolling speed of 1.5 m / s, reduction of 13% per pass, and holding time of 10 minutes per pass.
4. The method for controlling the strength and plasticity of FeMnCrCo high entropy alloys based on pre-introduction of multi-dimensional crystallographic defects according to claim 1, characterized in that: In step H), after the six hot rolling processes, a first cold rolling process is performed. The conditions of the first cold rolling process are: a reduction of 20% and a rolling speed of 0.3 m / s.
5. The method for controlling the strength and plasticity of FeMnCrCo high entropy alloys based on pre-introduction of multi-dimensional crystallographic defects according to claim 1, characterized in that: In step I), a first low-temperature annealing treatment is performed after the first cold rolling treatment. The conditions of the first low-temperature annealing treatment are: annealing temperature of 350° C.-400° C., holding time of 3 min-5 min, and cooling method of water cooling.
6. The method of claim 1 for controlling the strength and plasticity of FeMnCrCo high entropy alloys by pre-introducing multi-dimensional crystallographic defects, characterized in that: In step J), a second cold rolling process is performed after the first low-temperature annealing process. The conditions of the second cold rolling process are: a reduction of 25% and a rolling speed of 0.3 m / s.
7. The method of claim 1 for controlling the strength and plasticity of FeMnCrCo high entropy alloys by pre-introducing multi-dimensional crystallographic defects, characterized in that: In step K), a second low-temperature annealing treatment is performed after the second cold rolling treatment. The conditions of the second low-temperature annealing treatment are: annealing temperature of 350° C.-400° C., holding time of 3 min-5 min, and cooling method of water cooling.
8. The method of claim 1 for controlling the strength and plasticity of FeMnCrCo high entropy alloys by pre-introducing multi-dimensional crystallographic defects, characterized in that: In step L), a third cold rolling process is performed after the second low-temperature annealing process. The conditions of the third cold rolling process are: a reduction of 17% and a rolling speed of 0.3 m / s.
9. The method of claim 1 for controlling the strength and plasticity of FeMnCrCo high entropy alloys by pre-introducing multi-dimensional crystallographic defects, characterized in that: In step M), annealing is performed after the third cold rolling process. The annealing conditions are as follows: annealing temperature is 800° C.-1000° C., holding time is 3 min-20 min, and cooling method is water cooling.
10. A FeMnCrCo system metastable high entropy alloy, characterized in that: The method for controlling the strength and plasticity of FeMnCrCo-based high entropy alloys based on the pre-introduction of multi-dimensional crystallographic defects as described in any one of claims 1 to 9 is obtained.
Citation Information
Cited By
Rare earth cerium microalloyed high-strength toughness high-entropy alloy material and preparation method thereof
CN122105216A
A eutectic high-entropy alloy self-supporting catalytic electrode and a preparation method and application thereof
CN122466276A